Theoretical analysis of gas turbine blade by finite element method - Deepanraj, B; Lawrence, P; Sankaranarayanan, G (Scientific World, 2011)
Gas turbine is an important functional part of many applications. Cooling of blades has been a major concern since they are in a high temperature environment. Various techniques have been proposed for the cooling of blades and one such technique is to have axial holes along the blade span. Finite element analysis is used to analyze thermal and structural performance due to the loading condition, with material properties of Titanium- Aluminum Alloy. Six different models with different number of holes (7, 8, 9, 10, 11, and 12) were analyzed in this paper to find out the optimum number of holes for good performance. In Finite element analysis, first thermal analysis followed by structural analysis is carried out. Graphs are plotted for temperature distribution for existing design (12 holes) and for 8 holes against time. 2D and 3D model of the blade with cooling passages are shown. Using ANSYS, bending stress, deflection, temperature distribution for number of holes are analyzed. It is found that when the numbers of holes are increased in the blade, the temperature distribution falls down. For the blade configuration with 8 holes, the temperature near to the required value i.e., 800ºC is obtained. Thus a turbine blade with 8 holes configuration is found to be the optimum solution. Keywords: Gas turbine blade; Stress; Deflection; Temperature distribution. DOI: http://dx.doi.org/10.3126/sw.v9i9.5514 SW 2011; 9(9): 29-33